High-sand-carrying guanidine gum fracturing fluid system suitable for low-temperature preparation as well as preparation method and application of high-sand-carrying guanidine gum fracturing fluid system

By introducing the temperature regulators A WDTJ-A and B WDTJ-B into the guanidine glue fracturing fluid, the problem of slow cross-linking speed of guanidine glue fracturing fluid at low temperatures is solved, and high sand carrying performance and efficient construction are achieved, satisfying the The construction requirements of Russian oil and gas reservoirs were met.

CN119193133APending Publication Date: 2024-12-27四川瑞都石油工程技术服务有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411270012.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing guanidine glue fracturing fluid system is difficult to effectively crosslink under low temperature conditions, resulting in low construction efficiency and cannot meet the requirements of high sand carrying performance in Russian oil and gas reservoirs.

Method used

The temperature regulators A WDTJ-A and B WDTJ-B are introduced to improve the solubility and cross-linking speed of guanidine glue and boron minerals, and the high sand carrying performance of guanidine glue fracturing fluid at low temperatures is achieved, and guanidine collagen powder is used to thicken. The agent and the crosslinking agent are boron soda, etc. Combined with additives such as clay stabilizer and demulsifier, a high-sand-carrying guanidine glue fracturing liquid system suitable for low-temperature preparation is prepared.

Benefits of technology

The high sand carrying performance of guanidine glue fracturing fluid under low temperature conditions, shorten the cross-linking time, improve construction efficiency, and the stability and temperature resistance are better than traditional guanidine glue fracturing fluid, satisfying the Russian oil and gas reservoirs Construction parameters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193133A_ABST
    Figure CN119193133A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oil and gas reservoir fracturing transformation, in particular to a high-sand-carrying guanidine gum fracturing fluid system suitable for low-temperature preparation, which comprises guanidine gum, a temperature regulator A WDTJ-A, a temperature regulator B WDTJ-B and a cross-linking agent, each cubic meter of the high-sand-carrying guanidine gum fracturing fluid system comprises 3.2 to 3.6 kg of guanidine gum, 1.5 to 2.5 L of a temperature regulator A WDTJ-A, 0.5 to 1.0 L of a temperature regulator B WDTJ-B, 3.0 to 3.4 L of a cross-linking agent, and the balance of acceptable additives and water introduced in the preparation process of the guanidine gum fracturing fluid system. The method has the beneficial effects that the fracturing fluid system with high sand-carrying performance can be prepared at low temperature, and the problem that the construction efficiency is affected due to the fact that heating is needed in preparation of the existing guanidine gum fracturing fluid system with high sand-carrying performance in Russian is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas reservoir fracturing transformation, and in particular to a high-sand-carrying guar gum fracturing fluid system suitable for low-temperature preparation, a preparation method and application thereof. Background Art

[0002] Russia has rich oil and gas reserves, mainly low-permeability sandstone oil and gas reservoirs. Since low-permeability oil and gas reservoirs have low permeability, small porosity and low natural production capacity, it is necessary to transform the reservoir to improve the oil and gas conductivity and increase production.

[0003] At present, the transformation method mainly adopts hydraulic fracturing, and the fracturing fluid system used is guar gum fracturing fluid system. Single stage fluid volume 200-350m 3 , displacement 3.5-4m 3 / min; the proppant is mainly 16 / 20 mesh ceramsite, 30-90 tons of sand are added in a single stage, and the maximum sand concentration is 1000-1400kg / m 3 The construction scale is small, the construction displacement is low, the sand addition intensity is high, and the proppant particle size is large.

[0004] In order to ensure that the guar gum fracturing fluid system has excellent sand carrying performance, it is required to be at the reservoir temperature for 100s -1 Shear rate After shearing for 60-80 minutes, the liquid viscosity is greater than 400mPa.s; the liquid is at the reservoir temperature, 511s -1 High-speed shearing switch to 100s -1 After that, the viscosity recovers to more than 400mPa.s within 30s. In order to meet the above index requirements, the guar gum system currently used in Russia mainly uses guar gum powder as a thickener and one or more suspended boron minerals or borates as cross-linking agents. The gel strength is higher, and after rapid stirring, it still has good hanging properties, and it has better sand carrying capacity. However, the fracturing fluid system currently used in Russia does not cross-link in cold water, and the preparation water needs to be heated to 25-30°C before the cross-linking agent will cross-link with the guar gum base fluid. This results in a lot of time required to heat the preparation water when using this system, especially in the winter in Russia, and the construction efficiency is greatly reduced.

[0005] Existing literature has developed a low-concentration guar fracturing fluid system with a thickener concentration of 0.18%-0.2%. The thickener of this system is hydroxypropyl guar HPG, and the cross-linker is a self-developed low-concentration cross-linker QJL-B1. The cross-linker can introduce a charged group into the guar molecular chain. When the cross-linker and guar form a network structure, the repulsion between the charged groups is used to convert the contracted coils formed by the original guar cross-linking into stable extended coils, thereby increasing the network cross-linking volume of the cross-linker and guar, reducing the amount of guar required to form a cross-linked network, and at the same time does not change the sand carrying performance of the fracturing fluid. The thickener concentration of this system is 40%-50% lower than that of conventional guar fracturing. The system has good heat and shear resistance and filtration loss performance, with a damage rate of 22.53% to the core permeability and a residue content of 226.3 mg / L. However, during the field test of this system, the guar base fluid was prepared with room temperature water without heating. However, when the system is constructed on site, the construction displacement is 4.5-5m 3 / min, the sand ratio is 16-21%, and 20 / 40 mesh proppant is used. The sand carrying performance of the system cannot meet the sand concentration requirements of the current fracturing construction design in Russia.

[0006] The most commonly used guar gum fracturing fluid system in various oil fields at present mainly uses modified guar gum as a thickener, such as hydroxypropyl guar gum, and uses organic boron crosslinking agent, organic zirconium crosslinking agent or boron zirconium composite crosslinking agent as a crosslinking agent. As long as the mixing water can flow normally, this type of guar gum fracturing fluid system can directly prepare the fracturing fluid without heating. However, the sand carrying capacity of the currently used guar gum fracturing fluid system does not meet the requirements of Russia's current fracturing construction parameters, especially large particle size (16 / 20 mesh) and low displacement (3-4m 3 / min), high sand concentration (maximum sand concentration 1000-1400kg / m 3 ) requirements. Therefore, it is necessary to develop a high-sand-carrying guar gum fracturing fluid system suitable for low-temperature preparation and a preparation method thereof to meet the current fracturing construction requirements in Russia. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art, provide a high sand-carrying guar gum fracturing fluid system suitable for low-temperature preparation, and a preparation method and application thereof, and achieve the preparation of a fracturing fluid system with high sand-carrying performance at low temperature by introducing two additives, namely, a temperature regulator A WDTJ-A and a temperature regulator B WDTJ-B, into the guar gum system currently used in Russia, thereby solving the problem that the preparation of the guar gum fracturing fluid system with high sand-carrying performance currently used in Russia needs to be heated, thereby affecting the construction efficiency.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] The present disclosure provides a high-sand-carrying guar gum fracturing fluid system suitable for low-temperature preparation, including guar gum, temperature regulator B WDTJ-B, and a cross-linking agent;

[0010] The temperature regulator B WDTJ-B comprises the following components by weight: 10 to 15 parts of ethanolamine, 1 to 2 parts of sodium carbonate, 77 to 85 parts of water, 4 to 7 parts of fatty alcohol polyoxyethylene ether AEO-5 or 4 to 7 parts of fatty alcohol polyoxyethylene ether AEO-6 or 4 to 7 parts of fatty alcohol polyoxyethylene ether AEO-7.

[0011] Fatty alcohol polyoxyethylene ether (AEO), also known as polyoxyethylene fatty alcohol ether, is the fastest growing and most widely used type of non-ionic surfactant. This type of surfactant is an ether formed by the condensation of polyethylene glycol (PEG) and fatty alcohol, and is represented by the following general formula: RO(CH2CH2O)nH, where n is the degree of polymerization. There are different varieties due to the different degrees of polymerization of polyethylene glycol and the types of fatty alcohol.

[0012] In a preferred embodiment of the present scheme, each cubic meter of high sand-carrying guar gum fracturing fluid system includes: 3.2-3.6 kg of guar gum, 0.5-1.0 L of temperature regulator B WDTJ-B, 3.0-3.4 L of cross-linking agent, and the rest are acceptable additives and water introduced during the preparation of the guar gum fracturing fluid system.

[0013] The present disclosure also proposes a method for preparing a high-sand-carrying guar gum fracturing fluid system suitable for low-temperature preparation, comprising the following steps:

[0014] Step 1, uniformly dispersing the guar gum thickener in the liquid preparation water to obtain a pre-base liquid;

[0015] Step 2: Then, clay stabilizer, demulsifier, gel breaker and gel breaker activator are sequentially added to the pre-base fluid obtained in step 1, and stirred evenly to obtain guar gum fracturing fluid base fluid;

[0016] Step 3: Add a cross-linking agent to the guar gum fracturing fluid base fluid, and simultaneously add a temperature regulator B WDTJ-B, and stir evenly to obtain a guar gum fracturing fluid jelly system.

[0017] In a preferred embodiment of the present scheme, the additives in each cubic meter of high-sand-carrying guar gum fracturing fluid include 1.5 to 2.5 L of temperature regulator A WDTJ-A;

[0018] The temperature regulator A WDTJ-A comprises the following components by weight: 4 to 6 parts of fatty alcohol polyoxyethylene ether AOE-4, 4 to 5 parts of urea, and 89 to 92 parts of water.

[0019] In a preferred embodiment of the present scheme, the cross-linking agent is one or more of ulexite, colemanite, and borax; or the cross-linking agent is a suspension product prepared from one or more of ulexite, colemanite, and borax.

[0020] The cross-linking agent of the fracturing fluid system currently used in Russia is mainly one or more of boron minerals or borate minerals. For the organic boron cross-linking agent currently used by this cross-linking agent, the formed gel strength is stronger and the sand carrying capacity is stronger, but this type of cross-linking agent releases the cross-linking ions very slowly when the temperature is very low, so the preparation water needs to be heated during the on-site construction to accelerate the release rate of the cross-linking ions and boron ions, but the on-site construction efficiency is very low, and it consumes manpower and material resources. In the existing modified guar gum fracturing fluid, the cross-linking agent used is usually an organic boron cross-linking agent (organic boron cross-linking agent is obtained by the reaction of borate minerals with organic ligands and alkali), and the obtained gel strength and sand carrying capacity are poor, which cannot meet the current fracturing construction requirements of Russia.

[0021] In a preferred embodiment of the present scheme, in each cubic meter of high-sand-carrying guar gum fracturing fluid, the additives also include 1.0 to 3.0 L of liquid breaker and 0.0 to 1.0 L of breaker activator.

[0022] In a preferred embodiment of the present scheme, the breaker is one or more of 6-bromohexyl acetate, tert-butyl perbenzoate, sodium persulfate, ammonium persulfate, and capsule breaker.

[0023] In a preferred embodiment of the present scheme, the gel breaker activator is a metal coordination compound, in which the central atom is an iron ion and the ligands surrounding the iron ion are cyanide ions.

[0024] In a preferred embodiment of the present scheme, the metal coordination compound includes but is not limited to one of potassium ferrocyanide and sodium ferrocyanide.

[0025] In a preferred embodiment of the present scheme, in each cubic meter of high sand-carrying guar gum fracturing fluid, the additives further include 1.0 to 3.0 L of clay stabilizer and 1.0 to 3.0 L of demulsifier.

[0026] Adding clay stabilizers to the fracturing fluid helps prevent the hydration expansion and dispersion migration of clay minerals in the reservoir, protects the permeability of the reservoir, and helps enhance the fracturing effect.

[0027] Demulsifiers are added to the fracturing fluid to break the oil-water emulsion, separate the crude oil and water, reduce the flow resistance of the crude oil, and increase the oil well productivity. The choice of demulsifier depends on factors such as the composition of the fracturing fluid and the crude oil. Although demulsifiers play an important role in fracturing operations, they are not required in all cases. In some cases, such as when the crude oil itself has weak emulsification properties or during the fracturing of gas wells, demulsifiers may not be used.

[0028] The present disclosure also provides a method for preparing a high-sand-carrying guar gum fracturing fluid system suitable for low-temperature preparation, wherein the method comprises first preparing a fracturing fluid base fluid using guar gum powder as a thickener, and then adding a cross-linking agent to the guar gum fracturing fluid base fluid to prepare a guar gum fracturing fluid system;

[0029] When the cross-linking agent is added to the guar fracturing fluid base fluid, the temperature regulator B WDTJ-B as described above is also added.

[0030] In a preferred embodiment of the present scheme, the specific operation of preparing the fracturing fluid base fluid using guanidine collagen powder as a thickener includes: firstly adding the temperature regulator A WDTJ-A as mentioned above to the preparation water, and then adding guanidine collagen powder.

[0031] In a preferred embodiment of this scheme, the preparation method specifically comprises the following steps:

[0032] S1. Evenly disperse the temperature regulator A WDTJ-A and the guar gum thickener in the liquid preparation water to obtain a pre-base liquid;

[0033] S2, then sequentially add clay stabilizer, demulsifier, gel breaker and gel breaker activator to the pre-base fluid, stir evenly, and obtain guar gum fracturing fluid base fluid;

[0034] S3. Add a cross-linking agent to the guar gum fracturing fluid base fluid, and simultaneously add a temperature regulator B WDTJ-B, and stir evenly to obtain a guar gum fracturing fluid jelly system.

[0035] In a preferred embodiment of the present scheme, the specific operation of step S1 is: measuring the preparation water and pouring it into the stirrer, turning on the stirrer, adding the temperature regulator A WDTJ-A, and then adding the guar gum thickener, stirring for 2 to 3 minutes; and standing for 10 minutes.

[0036] The preparation of the high-sand-carrying guar gum fracturing fluid system disclosed in the present invention can adapt to low-temperature preparation water of 0 to 20°C.

[0037] An application of the above-mentioned high-sand-carrying guar gum fracturing fluid system or the high-sand-carrying guar gum fracturing fluid system prepared by the above-mentioned preparation method in the fracturing development of oil and gas reservoirs.

[0038] When the temperature regulator A WDTJ-A is added into water, the surface tension of water decreases and surfactant aggregates can be formed. The aggregates selectively gather the undissolved guar gum at one end of the hydrophilic group, which can improve the solubility of the original powdered guar gum currently used in Russia. At the same time, with the addition of the temperature regulator A WDTJ-A, the interfacial tension of the solution becomes smaller, the guar gum molecules are evenly dispersed in the solution, and the guar gum molecular chain stretches rapidly in cold water, accelerating its dissolution in low-temperature water, especially in water below 10°C, exposing the cis-ortho hydroxyl groups on the molecular chain.

[0039] Temperature regulator B WDTJ-B can reduce the interfacial tension of aqueous solution, accelerate the penetration of water molecules into boron minerals, and thus accelerate the dissolution of boron minerals; WDTJ-B is alkaline, and boron minerals are hydrolyzed to produce hydrogen ions, which will accelerate the hydrolysis of boron minerals and the release of boron ions. It can quickly cross-link with guar gum at low temperatures, achieving the same performance as guar gum jelly prepared with 25-30℃ liquid water, thereby solving the problem that the preparation of the guar gum fracturing fluid system with high sand carrying performance currently used in Russia needs to be heated, thus affecting the construction efficiency.

[0040] The term "pre-base fluid" refers to the base fluid of the fracturing fluid when the thickener is dispersed in the mixing water and additives such as clay stabilizers and demulsifiers have not yet been added.

[0041] The beneficial effects of the present invention are:

[0042] The present invention introduces two additives, namely, a temperature regulator A WDTJ-A and a temperature regulator B WDTJ-B, into the guar gum system currently used in Russia. The temperature regulator A WDTJ-A is added into water to improve the solubility of the original powdered guar gum currently used in Russia, and is conducive to the uniform dispersion of guar gum molecules in the solution, and accelerates the dissolution of guar gum molecules in low-temperature water, especially in water below 10°C; the temperature regulator B WDTJ-B can reduce the interfacial tension of the aqueous solution, accelerate the penetration of water molecules into boron minerals, and accelerate the dissolution of boron minerals; the temperature regulator B WDTJ-B is alkaline, and can accelerate the hydrolysis and release of boron minerals, and thus the present invention can quickly cross-link with guar gum at low temperature, and achieve the same performance as guar gum jelly prepared by preparing liquid water at 25-30°C, thereby solving the problem that the preparation of the guar gum fracturing fluid system with high sand carrying performance currently used in Russia needs to be heated, thereby affecting the construction efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The graph is a graph showing the viscosity test results of the guar gum solution at different times in Experimental Example 1;

[0044] Figure 2 For Experimental Example 1 3.2kg / m 3 Viscosity requirements of guar gum at different temperatures;

[0045] Figure 3The graph is a graph showing the viscosity test results of the guar gum solution at different times in Experimental Example 2;

[0046] Figure 4 For Experimental Example 2 3.4kg / m 3 Viscosity requirements of guar gum at different temperatures

[0047] Figure 5 The graph is a graph showing the viscosity test results of the guar gum solution at different times in Experimental Example 3;

[0048] Figure 6 For Experiment 3, 3.6 kg / m 3 Viscosity requirements of guar gum at different temperatures

[0049] Figure 7 The graph is a viscosity test result of the fracturing fluid system of Example 4 at different times;

[0050] Figure 8 The graph is a viscosity test result of the fracturing fluid system of Comparative Example 3 at different times;

[0051] Fig. 9 The graph is a viscosity test result of the fracturing fluid system of Comparative Example 4 at different times;

[0052] Fig.10 This is a graph showing the viscosity test results of the fracturing fluid system of Example 8 at different times. DETAILED DESCRIPTION

[0053] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following.

[0054] Example

[0055] Prepare various temperature regulators A WDTJ-A and various temperature regulators B WDTJ-B according to the following formula:

[0056] Temperature regulator A WDTJ-A 1#: 4% fatty alcohol polyoxyethylene ether AEO-4 + 4% urea + 89%-92% water;

[0057] Temperature regulator A WDTJ-A 2#: 6% fatty alcohol polyoxyethylene ether AEO-4 + 5% urea + 89%-89% water;

[0058] Temperature regulator A WDTJ-A 3#: 5% fatty alcohol polyoxyethylene ether AEO-4 + 5% urea + 89%-89% water;

[0059] Temperature regulator B WDTJ-B 1#: 4% fatty alcohol polyoxyethylene ether AEO-5 + 15% ethanolamine + 1% sodium carbonate + 80% water;

[0060] Temperature regulator B WDTJ-B 2#: 5% fatty alcohol polyoxyethylene ether AEO-5 + 10% ethanolamine + 2% sodium carbonate + 83% water;

[0061] Temperature regulator B WDTJ-B 3#: 7% fatty alcohol polyoxyethylene ether AEO-5 + 15% ethanolamine + 1% sodium carbonate + 77% water;

[0062] Temperature regulator B WDTJ-B 4#: 5% fatty alcohol polyoxyethylene ether AEO-6 + 10% ethanolamine + 2% sodium carbonate + 83% water;

[0063] Temperature regulator B WDTJ-B 5#: 5% fatty alcohol polyoxyethylene ether AEO-7 + 10% ethanolamine + 2% sodium carbonate + 83% water.

[0064] Experimental Example 1

[0065] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 1.0L / m 3 , 1.5L / m 3 , 2.0L / m 3 , 2.5L / m 3 、3.0L / m 3 Temperature regulator A WDTJ-A 1#, and then add 3.2L / m 3 After stirring for 30 seconds, transfer the liquid into the rheometer measuring cup; set the test temperature to 10°C and the shear rate to 511s -1 After adding different concentrations of temperature regulator A WDTJ-A 1#, the viscosity of guar gum solution at different times was tested. The test results are as follows: Figure 1 shown.

[0066] 3.2kg / m 3 The viscosity requirements of guar gum at different temperatures are shown in the following chart: Figure 2 shown.

[0067] Experimental Example 2

[0068] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 1.0L / m 3 , 1.5L / m 3 , 2.0L / m 3 , 2.5L / m 3 、3.0L / m 3 Temperature regulator A WDTJ-A 2#, and then add 3.4L / m3 After stirring for 30 seconds, transfer the liquid into the rheometer measuring cup; set the test temperature to 10°C and the shear rate to 511s -1 After adding different concentrations of temperature regulator A WDTJ-A 2#, the viscosity of guar gum solution at different times was tested. The test results are as follows: Figure 3 shown.

[0069] 3.4kg / m 3 The viscosity requirements of guar gum at different temperatures are shown in the following chart: Figure 4 shown.

[0070] Experimental Example 3

[0071] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 1.0L / m 3 , 1.5L / m 3 , 2.0L / m 3 , 2.5L / m 3 、3.0L / m 3 Temperature regulator A WDTJ-A3#, and then add 3.6L / m 3 After stirring for 30 seconds, transfer the liquid into the rheometer measuring cup; set the test temperature to 10°C and the shear rate to 511s -1 After adding different concentrations of temperature regulator AWDTJ-A 3#, the viscosity of guar gum solution at different times was tested. The test results are as follows: Figure 5 As shown. 3.6kg / m 3 The viscosity requirements of guar gum at different temperatures are shown in the following figure: Figure 6 shown.

[0072] Example 1

[0073] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 2.0L / m 3 Temperature regulator A WDTJ-A2#, then add 3.4L / m 3 After stirring for 3 minutes, pour the liquid into a beaker and place it in a 10°C refrigerator. After standing for 10 minutes, take it out and pour it into the blender. Continue to add 2L / m 3 Quaternary ammonium salt clay stabilizer NG CS-1 (produced by NG Chemical Co., Ltd.), 2L / m 3 Polyether demulsifier NG NE-1 (produced by NG Chemical Co., Ltd.) and 1.0L / m 3Gel breaker NG OB-3 (0.5% 6-bromohexyl acetate + 1% tert-butyl perbenzoate, produced by NG Chemical Co., Ltd.), 0.5L / m 3 The gel breaker activator NG OBA (4% potassium ferrocyanide solution, produced by NG Chemical Company) was stirred for 2 minutes to prepare the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was seen. 0.5 L / m 3 , 0.8L / m 3 , 1.0L / m 3 , 1.2L / m 3 Temperature regulator B WDTJ-B 1# and 3.2L / m 3 The crosslinking agent NG XL-2 (50% ulexite suspension, produced by NG Chemical Company) was used. The timing was started and the vortex closing time was recorded. When the vortex was closed, the liquid was poured into a beaker and continuously shaken to observe the liquid tongue-out time. The experimental results are shown in Table 1.

[0074] Example 2

[0075] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 2.0L / m 3 Temperature regulator A WDTJ-A 2#, then add 3.4L / m 3 After stirring for 3 minutes, pour the liquid into a beaker and place it in a 10°C refrigerator. After standing for 10 minutes, take it out and pour it into the blender. Continue to add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier and 1.0L / m 3 Gel breaker, 0.5L / m 3 The gel breaker activator was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. 0.5 L / m 3 , 0.8L / m 3 , 1.0L / m 3 , 1.2L / m 3 Temperature regulator B WDTJ-B 2# and 3.2L / m 3 The cross-linking agent was added, and the timing was started to record the vortex closing time. When the vortex was closed, the liquid was poured into the beaker, and the beaker was shaken continuously to observe the time when the liquid stuck out of the tongue. The experimental results are shown in Table 1. (The chemicals are the same as those in Example 1)

[0076] Example 3

[0077] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 2.0L / m 3 Temperature regulator AWDTJ-A 2#, then add 3.4L / m 3 After stirring for 3 minutes, pour the liquid into a beaker and place it in a 10°C refrigerator. After standing for 10 minutes, take it out and pour it into the blender. Continue to add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier and 1.0L / m 3 Gel breaker, 0.5L / m 3 The gel breaker activator was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. 0.5 L / m 3 , 0.8L / m 3 , 1.0L / m 3 , 1.2L / m 3 Temperature regulator B WDTJ-B 3# and 3.2L / m 3 The cross-linking agent was added, and the timing was started to record the vortex closing time. When the vortex was closed, the liquid was poured into the beaker, and the beaker was shaken continuously to observe the time when the liquid stuck out of the tongue. The experimental results are shown in Table 1. (The chemicals are the same as those in Example 1)

[0078] Table 1 Test results of vortex closure time and liquid tongue-out time

[0079]

[0080]

[0081] Example 4

[0082] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 2.0L / m 3 Temperature regulator A WDTJ-A 2#, then add 3.4L / m 3 After stirring for 3 minutes, pour the liquid into a beaker and place it in a 10°C refrigerator. After standing for 10 minutes, take it out and pour it into the blender. Continue to add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier, 0.5L / m 3 Gel breaking activator, and then add 1.0L / m 3 , 1.5L / m 3 , 2.0L / m 3The gel breaker was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. At the same time, 0.8 L / m 3 Temperature regulator B WDTJ-B 2# and 3.2L / m 3 Crosslinker, when the vortex is closed, pour the liquid into the beaker and shake it continuously. When the liquid starts to spit out, take a sample and put it into the rheometer. Set the test temperature to 85℃ and the shear rate to 100s. -1 , constant temperature shear 90min, the test results are as follows Figure 7 shown.

[0083] (Chemicals are the same as in Example 1)

[0084] Example 5

[0085] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 2.0L / m 3 Temperature regulator A WDTJ-A 2#, then add 3.4L / m 3 After stirring for 3 minutes, pour the liquid into a beaker and place it in a 10°C refrigerator. After standing for 10 minutes, take it out and pour it into the blender. Continue to add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier, 1.0L / m 3 Gel breaker, 0.5L / m 3 The gel breaker activator was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. At the same time, 0.8 L / m 3 Temperature regulator B WDTJ-B 2#, 3.2L / m 3 The cross-linking agent and 300g of 16 / 20 mesh ceramsite were stirred until the liquid level was raised, the sand-carrying liquid was poured into a 500ml measuring cylinder, the measuring cylinder was placed in a 90℃ water bath, and the time taken for the ceramsite to completely settle was recorded. The results are shown in Table 2.

[0086] Example 6

[0087] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 2.0L / m 3 Temperature regulator A WDTJ-A 2#, then add 3.4L / m 3 After stirring for 3 minutes, pour the liquid into a beaker and place it in a 10°C refrigerator. After standing for 10 minutes, take it out and pour it into the blender. Continue to add 2L / m 3Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier, 1.0L / m 3 Gel breaker, 0.5L / m 3 The gel breaker activator was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. At the same time, 0.8 L / m 3 Temperature regulator B WDTJ-B 4#, 3.2L / m 3 The cross-linking agent and 300g of 16 / 20 mesh ceramsite were stirred until the liquid surface was raised, the sand-carrying liquid was poured into a 500ml measuring cylinder, the measuring cylinder was placed in a 90°C water bath, and the time taken for the ceramsite to completely settle was recorded. The results are shown in Table 2. (The chemicals are the same as in Example 1)

[0088] Example 7

[0089] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 2.0L / m 3 Temperature regulator A WDTJ-A 2#, then add 3.4L / m 3 After stirring for 3 minutes, pour the liquid into a beaker and place it in a 10°C refrigerator. After standing for 10 minutes, take it out and pour it into the blender. Continue to add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier, 1.0L / m 3 Gel breaker, 0.5L / m 3 The gel breaker activator was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. At the same time, 0.8 L / m 3 Temperature regulator B WDTJ-B 5#, 3.2L / m 3 The cross-linking agent and 300g of 16 / 20 mesh ceramsite were stirred until the liquid surface was raised, the sand-carrying liquid was poured into a 500ml measuring cylinder, the measuring cylinder was placed in a 90°C water bath, and the time taken for the ceramsite to completely settle was recorded. The results are shown in Table 2. (The chemicals are the same as in Example 1)

[0090] Example 8

[0091] The tap water was cooled to 10°C, and the following fracturing fluid gels were prepared according to the preparation method of the high-carrying guar gum fracturing fluid system disclosed in the present invention. (The preparation steps and chemicals are the same as those in Example 1)

[0092] 3.4kg / m 3 Guar gum +2.0L / m 3 Temperature regulator AWDTJ-A 2#+2.0L / m 3Clay stabilizer + 1.0L / m 3 Demulsifier + 0.8L / m 3 Temperature regulator B WDTJ-B 2#+3.2L / m 3 Cross-linking agent + 1.0L / m 3 Liquid breakers;

[0093] 3.4kg / m 3 Guar gum +2.0L / m 3 Temperature regulator AWDTJ-A 2#+2.0L / m 3 Clay stabilizer + 1.0L / m 3 Demulsifier + 3.2L / m 3 Cross-linking agent + 1.0L / m 3 Liquid breakers;

[0094] 3.4kg / m 3 Guar gum +2.0L / m 3 Clay stabilizer + 1.0L / m 3 Demulsifier + 0.8L / m 3 Temperature regulator B WDTJ-B2#+3.2L / m 3 Cross-linking agent + 1.0L / m 3 Liquid breakers;

[0095] 3.4kg / m 3 Guar gum +2.0L / m 3 Clay stabilizer + 1.0L / m 3 Demulsifier + 3.2L / m 3 Cross-linking agent + 1.0L / m 3 Liquid breakers.

[0096] The jelly samples prepared by each recipe in this embodiment were placed in a rheometer, and the test temperature was set to 85°C, the shear rate was 100s-1, and the constant temperature shearing was performed for 90min. The test results are shown in FIG. Fig.10 shown.

[0097] Example 9

[0098] Cool the tap water to 5℃, measure 300ml of 5℃ tap water and pour it into the waring mixer, adjust the mixer speed until the bottom center axis can be seen, and add 2.0L / m 3 Temperature regulator A WDTJ-A 2#, then add 3.4L / m 3 After stirring for 3 minutes, pour the liquid into a beaker and place it in a 5°C refrigerator. After standing for 10 minutes, take it out and pour it into the blender. Continue to add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3Demulsifier, 1.0L / m 3 Gel breaker, 0.5L / m 3 The gel breaker activator was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. At the same time, 0.8 L / m 3 Temperature regulator B WDTJ-B 2#, 3.2L / m 3 The cross-linking agent and 300g of 16 / 20 mesh ceramsite were stirred until the liquid surface was raised, the sand-carrying liquid was poured into a 500ml measuring cylinder, the measuring cylinder was placed in a 90°C water bath, and the time taken for the ceramsite to completely settle was recorded. The results are shown in Table 2. (The chemicals are the same as in Example 1)

[0099] Comparative Example 1

[0100] Heat tap water to 30℃, measure 300ml of 30℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 3.4L / m 3 After stirring for 13 minutes, add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier and 1.0L / m 3 Gel breaker, 0.5L / m 3 The gel breaker activator was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. 3.2 L / min was added. 3 The cross-linking agent was added, and the timing was started to record the vortex closing time. When the vortex was closed, the liquid was poured into the beaker, and the beaker was shaken continuously to observe the time when the liquid stuck out of the tongue. The experimental results are shown in Table 1. (The chemicals are the same as those in Example 1)

[0101] Comparative Example 2

[0102] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 3.4L / m 3 After stirring for 3 minutes, pour the liquid into a beaker and place it in a 10°C refrigerator. After standing for 10 minutes, take it out and pour it into the blender. Continue to add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier and 1.0L / m 3 Gel breaker, 0.5L / m 3 The gel breaker activator was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. 3.2 L / min was added. 3The cross-linking agent was added, and the timing was started to record the vortex closing time. When the vortex was closed, the liquid was poured into the beaker, and the beaker was shaken continuously to observe the time when the liquid stuck out of the tongue. The experimental results are shown in Table 1. (The chemicals are the same as those in Example 1)

[0103] Comparative Example 3

[0104] Heat tap water to 30℃, measure 300ml of 30℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 3.4L / m 3 After stirring for 13 minutes, add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier, 0.5L / m 3 Gel breaking activator, and then add 1.0L / m 3 , 1.5L / m 3 , 2.0L / m 3 The gel breaker was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. 3.2 L / m 3 Crosslinker, when the vortex is closed, pour the liquid into the beaker and shake it continuously. When the liquid starts to spit out, take a sample and put it into the rheometer. Set the test temperature to 85℃ and the shear rate to 100s. -1 , constant temperature shear 90min, the test results are as follows Figure 8 As shown. (The chemical code is the same as that in Example 1)

[0105] Comparative Example 4

[0106] Measure 300ml of room temperature tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 3.4L / m 3 After stirring for 13 minutes, add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier, 1.0L / m 3 Gel breaking, 0.5L / m 3 Gel breaking activator, 0.1% NaOH aqueous solution (10% NaOH), stir for 2 minutes; prepare the base liquid, adjust the speed of the stirrer until the center axis of the stirrer is seen, add 3.2L / m 3 Organic boron crosslinker (produced by PetroChina Sichuan Qing Downhole Technology Company). When the vortex is closed, pour the liquid into the beaker and shake it continuously. When the liquid starts to spit out the tongue, take a sample and put it into the rheometer. Set the test temperature to 85℃ and the shear rate to 100s. -1 , constant temperature shear 90min, the test results are as follows Fig. 9 As shown. (The chemical code is the same as that in Example 1)

[0107] Comparative Example 5

[0108] Heat tap water to 30℃, measure 300ml of 30℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration, add 3.4L / m 3 After stirring for 13 minutes, add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier, 1.0L / m 3 Gel breaker, 0.5L / m 3 The gel breaker activator was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. 3.2 L / min was added. 3 Add cross-linking agent and 300g 16 / 20 mesh ceramsite, stir until the liquid level rises, pour the sand-carrying liquid into a 500ml measuring cylinder, put the measuring cylinder into a 90℃ water bath, and record the time taken for the ceramsite to completely settle. The results are shown in Table 2.

[0109] Comparative Example 6

[0110] Measure 300ml of room temperature tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. According to the volume concentration meter, add 3.4L / m 3 After stirring for 13 minutes, add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier, 1.0L / m 3 Gel breaking, 0.5L / m 3 The gel breaker activator and 0.1% NaOH aqueous solution (10% NaOH) were stirred for 2 minutes to obtain the base solution. The speed of the stirrer was adjusted until the center axis of the stirrer was visible. 3.2 L / min was added. 3 Organic boron crosslinking agent (produced by PetroChina Sichuan Qing Downhole Technology Company) and 300g 16 / 20 mesh ceramsite were stirred until the liquid surface was convex, the sand-carrying liquid was poured into a 500ml measuring cylinder, and the measuring cylinder was placed in a 90℃ water bath. The time taken for the ceramsite to completely settle was recorded. The results are shown in Table 2.

[0111] Table 2 Test results of ceramsite settling time

[0112]

[0113] Comparative Example 7

[0114] Cool the tap water to 10℃, measure 300ml of 10℃ tap water and pour it into the waring mixer. Adjust the mixer speed until the bottom center axis is visible. Add 2.0L / m3 Temperature regulator A WDTJ-A 2#, stir evenly, then continue to add 3.4L / m 3 After stirring for 3 minutes, pour the liquid into a beaker and place it in a 10°C refrigerator. After standing for 10 minutes, take it out and pour it into the blender. Continue to add 2L / m 3 Quaternary ammonium salt clay stabilizer, 2L / m 3 Demulsifier and 1.0L / m 3 Gel breaker, 0.5L / m 3 The gel breaker activator was stirred for 2 minutes to obtain the base liquid. The speed of the agitator was adjusted until the center axis of the bottom of the agitator was visible. 3.2 L / min was added. 3 The cross-linking agent was added, and the timing was started to record the vortex closing time. When the vortex was closed, the liquid was poured into the beaker, and the beaker was shaken continuously to observe the time when the liquid stuck out of the tongue. The experimental results are shown in Table 1. (The chemicals are the same as those in Example 1)

[0115] Summarize:

[0116] It can be seen from Experimental Examples 1 to 3 that as the amount of temperature regulator A WDTJ-A increases, the viscosity of the guar gum powder after complete dissolution shows a trend of first increasing and then decreasing. The addition of temperature regulator A WDTJ-A can accelerate the dissolution of guar gum and increase the viscosity of guar gum after complete dissolution. According to the viscosity chart after complete dissolution corresponding to different concentrations of guar gum, the addition range of temperature regulator AWDTJ-A is 1.5L / m 3 ~2.5L / m 3 .

[0117] Through Examples 1 to 3 and Comparative Examples 1 and 2, it can be seen that the temperature regulator B WDTJ-B can accelerate the cross-linking of the guar gum solution under low temperature conditions, shorten the vortex closing time and the tongue-out time of the gum solution, that is, accelerate the cross-linking. By adjusting the amount of the temperature regulator B WDTJ-B, the vortex closing time and the tongue-out time can be adjusted to achieve the effect of liquid cross-linking after the liquid is heated. The range of the temperature regulator B WDTJ-B addition is 0.5L / m 3 ~1.0L / m 3 .

[0118] It can be seen from Example 4 and Comparative Examples 3 and 4 that after adding temperature regulator A WDTJ-A and temperature regulator B WDTJ-B, the stability of the guar gum system prepared under low temperature conditions at reservoir temperature is consistent with the stability of the guar gum system prepared with 30°C liquid water; it also has good temperature resistance so that it can achieve the effect of high sand carrying; the stability and temperature and shear resistance of the above two systems are better than those of the guar gum fracturing fluid formed by organic boron cross-linking agents.

[0119] It can be seen from Example 4 that by changing the amount of breaker added, the speed of liquid breaking can be controlled. During the on-site construction process, the breaker concentration can be designed in a wedge shape according to the construction sand adding steps, so that the liquid can be broken and quickly returned after the construction is completed while ensuring smooth construction.

[0120] It can be seen from the test results of Example 5 and Comparative Examples 5 and 6 that after adding temperature regulator A WDTJ-A and temperature regulator B WDTJ-B, the sand-carrying capacity of the guar gum system prepared under low temperature conditions at reservoir temperature is consistent with the sand-carrying capacity of the guar gum system prepared with 30°C liquid water, and both are better than the guar gum fracturing fluid formed by the organic boron cross-linking agent.

[0121] It can be seen from Example 8 that the guar gum fracturing fluid system with both temperature regulator A WDTJ-A and temperature regulator B WDTJ-B added to the low-temperature preparation water has the best stability; the second is without adding temperature regulator A WDTJ-A and adding temperature regulator B WDTJ-B; the third is adding temperature regulator A WDTJ-A and not adding temperature regulator B WDTJ-B; the worst is without adding temperature regulator A WDTJ-A and temperature regulator B WDTJ-B.

[0122] It can be seen from the above embodiments and comparative examples that the introduction of temperature regulator A WDTJ-A and temperature regulator B WDTJ-B can accelerate the crosslinking of the existing Russian guar gum fracturing fluid with high sand carrying capacity, shorten the vortex closure time and tongue sticking time; at the same time, the stability performance of the whole system is consistent with the guar gum system prepared with 30°C liquid water, and the system also has a high sand carrying capacity, thereby solving the problem of the need to heat the liquid water of the current Russian guar gum system, and can effectively improve the on-site construction efficiency.

[0123] The embodiments and experimental examples of this scheme are all carried out at room temperature of 20°C; however, it should be noted that since the change of ambient temperature has a negligible effect on the density of each raw material within the operable ambient temperature range, the present disclosure uses volume concentration as the ratio, and there is no obvious difference in the properties of the product system obtained at different ambient temperatures, which will not be discussed in detail in this disclosure.

[0124] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

Claims

1. A high-sand-carrying guar gum fracturing fluid system suitable for low-temperature preparation, characterized in that: Including guar gum, temperature regulator B WDTJ-B, and cross-linking agent; The temperature regulator B WDTJ-B comprises the following components in parts by weight: 10-15 parts of ethanolamine, 1-2 parts of sodium carbonate, 77-85 parts of water, 4-7 parts of fatty alcohol polyoxyethylene ether AEO-5 or 4-7 parts of fatty alcohol polyoxyethylene ether AEO-6 or 4-7 parts of fatty alcohol polyoxyethylene ether AEO-7.

2. The high sand-carrying guar gum fracturing fluid system according to claim 1, characterized in that: Each cubic meter of high sand-carrying guar gum fracturing fluid system includes: 3.2-3.6 kg guar gum, 0.5-1.0 L temperature regulator B WDTJ-B, 3.0-3.4 L cross-linking agent, and the rest are acceptable additives and water introduced in the preparation process of the guar gum fracturing fluid system.

3. The high sand-carrying guar gum fracturing fluid system according to claim 2, characterized in that: In each cubic meter of high-sand-carrying guar gum fracturing fluid, the additives include 1.5 to 2.5 L of temperature regulator AWDTJ-A; The temperature regulator AWDTJ-A comprises the following components by weight: 4-6 parts of fatty alcohol polyoxyethylene ether AOE-4, 4-5 parts of urea, 89-92 parts of water.

4. A high sand-carrying guar gum fracturing fluid system suitable for low temperature preparation according to any one of claims 1 to 3, characterized in that: The cross-linking agent is one or more of ulexite, colemanite, and borax; or The cross-linking agent is a suspension product prepared from one or more of ulexite, colemanite and borax.

5. The high sand-carrying guar gum fracturing fluid system according to any one of claims 1 to 3, characterized in that: In each cubic meter of high-sand-carrying guar gum fracturing fluid, the additives also include 1.0 to 3.0 L of a breaker and 0.0 to 1.0 L of a breaker activator.

6. A high-sand-carrying guar gum fracturing fluid system suitable for low-temperature preparation according to claim 5, characterized in that: The gel breaker is one or more of 6-bromohexyl acetate, tert-butyl perbenzoate, sodium persulfate, ammonium persulfate, and capsule gel breaker.

7. The high sand-carrying guar gum fracturing fluid system suitable for low temperature preparation according to claim 5, characterized in that: The gel breaker activator is a metal coordination compound, in which the central atom is an iron ion and the ligands surrounding the iron ion are cyanide ions; The metal coordination compound includes but is not limited to one of potassium ferrocyanide and sodium ferrocyanide.

8. A method for preparing a high-sand-carrying guar gum fracturing fluid system suitable for low-temperature preparation, characterized in that: The method is to first prepare a fracturing fluid base fluid by using guar gum powder as a thickener, and then add a cross-linking agent to the guar gum fracturing fluid base fluid to prepare a guar gum fracturing fluid system; When the cross-linking agent is added to the guar gum fracturing fluid base fluid, the temperature regulator B WDTJ-B as described in any one of claims 1 to 7 is also added.

9. The preparation method according to claim 8, characterized in that: The specific operations of preparing fracturing fluid base fluid using guanidine collagen powder as thickener include: First, add the temperature regulator AWDTJ-A as described in any one of claims 3 to 7 to the preparation water, and then add the guanidine collagen powder.

10. The preparation method according to claim 8, characterized in that: The specific steps include: S1. Evenly disperse the temperature regulator AWDTJ-A and guar gum thickener in the liquid preparation water to obtain a pre-base liquid; S2, then sequentially add clay stabilizer, demulsifier, gel breaker and gel breaker activator to the pre-base fluid, stir evenly, and obtain guar gum fracturing fluid base fluid; S3. Add a cross-linking agent to the guar gum fracturing fluid base fluid, and simultaneously add a temperature regulator B WDTJ-B, and stir evenly to obtain a guar gum fracturing fluid jelly system.

11. The preparation method according to claim 10, characterized in that: The specific operation of step S1 is: measure the preparation water and pour it into the stirrer, turn on the stirrer, add the temperature regulator AWDTJ-A, then add the guar gum thickener, stir for 2 to 3 minutes; and let it stand for 10 minutes.

12. Use of the high-sand-carrying guar gum fracturing fluid system according to any one of claims 1 to 3 or the high-sand-carrying guar gum fracturing fluid system prepared by the preparation method according to any one of claims 8 to 11 in the fracturing development of oil and gas reservoirs.